Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4314/ahs.v14i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Brucella sero-prevalence and modifiable risk factors among predisposed cattle keepers and consumers of un-pasteurized milk in Mbarara and Kampala districts, Uganda

Abstract: Abstract:Background: Brucellosis is an important zoonotic disease in developing countries yet it is often not recognized, goes unreported and does not attract public health action by these governments including Uganda. Objective: To estimate the sero-prevalence and assess modifiable risk factors associated with Brucella seropositivity in cattle keepers and consumers of unpasteurized milk in Uganda. Methods: One group comprised of 161 individuals randomly selected from households living on farms that had Brucel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 8 publications
2
26
0
2
Order By: Relevance
“…Among the bacterial diseases of cattle, mastitis was the most frequently diagnosed disease ( Table 3 ), this was in agreement with previous studies [16] , [17] that reported a prevalence of over 50%. Brucellosis was also frequently diagnosed at CDL (23%), consistent with earlier reports [18] , [19] , [20] , [21] . Nutritional diseases were more frequently diagnosed in chicken compared to cattle.…”
Section: Discussionsupporting
confidence: 91%
“…Among the bacterial diseases of cattle, mastitis was the most frequently diagnosed disease ( Table 3 ), this was in agreement with previous studies [16] , [17] that reported a prevalence of over 50%. Brucellosis was also frequently diagnosed at CDL (23%), consistent with earlier reports [18] , [19] , [20] , [21] . Nutritional diseases were more frequently diagnosed in chicken compared to cattle.…”
Section: Discussionsupporting
confidence: 91%
“…22,23,26 Lack of knowledge of the transmission and symptoms of brucellosis was found in 88.4% of the respondents in the present study, but it was not significantly associated with seropositivity. Related investigations have reported high lack of awareness and knowledge of brucellosis in Tajikistan (85%), 27 Nigeria (78.5%), 28 and Uganda (69.6%), 29 while in one study in Kenya up to 78% of the respondents did not know that brucellosis existed. 30 In some instances, limited awareness of brucellosis of the community has been attributed to the absence of its diagnosis and treatment at the health facilities and instead other febrile conditions such as malaria and typhoid being the most commonly mentioned and managed.…”
Section: Discussionmentioning
confidence: 94%
“…This is not surprising given that the role of raw milk in the transmission of brucellosis has been reported in several studies. 22,24,29,33,34 Raw milk consumption has been on the increase not only in Rwanda but also in other countries in the region, owing to the increasing costs of milk processing, which has resulted in closure of some plants in some countries. 14,35 As a result, unpasteurized fermented milk sold by such outlets as restaurants, small shops, and street vendors expose consumers to milk-borne diseases including brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence of 4.0% and 13.0% were obtained for Katsina and Sokoto States respectively based on c-ELISA. Evidence of B. melitensis antibodies in the animals under study may be of public health importance as it is the most pathogenic species for man resulting in long term debilitation (Nasinyama et al, 2014). In most villages in Northern Nigeria, small ruminants make up the bulk of animal protein supply.…”
Section: Discussionmentioning
confidence: 99%